Fault detection in three phase induction motor using artificial intelligence - Ahmad Farid, Abu Bakar (2009)
Artificial intellegence (AI) techniques have proved their ability in detection of incipient faults in electrical machines. in this project, the fault diagnosis of three phase induction motors is studied detailed in unbalance voltage and stator inter turn fault using simulation models and neural networks have been used to train the data using Radial Basis Function Neural Network (RBFNN) in MATLAB with Graphical USer Interface Development Environment (GUIDE) structured.